2016
DOI: 10.1038/eye.2016.127
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue inhibits migration of ocular surface epithelial cells

Abstract: PurposeFibrin glue has been used successfully in numerous ophthalmic surgical procedures. Recently, fibrin glue has been used in limbal stem cell transplantation to reduce both operative time and to negate the need for sutures. The aim of this study was to determine the effects of fibrin glue on epithelial cell migration in vitro.MethodsCorneoscleral rims were split to retain the epithelial layer, Bowman's layer, and anterior stroma. Rims were cut into eight equal-sized pieces and were placed directly on cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
(25 reference statements)
1
39
1
Order By: Relevance
“…Fibrin glue has been shown to mechanically interfere with epithelial cell migration which proceeds normally once the glue dissolves in 10-14 days (Yeung et al 2016). Fibrin glue has been shown to mechanically interfere with epithelial cell migration which proceeds normally once the glue dissolves in 10-14 days (Yeung et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrin glue has been shown to mechanically interfere with epithelial cell migration which proceeds normally once the glue dissolves in 10-14 days (Yeung et al 2016). Fibrin glue has been shown to mechanically interfere with epithelial cell migration which proceeds normally once the glue dissolves in 10-14 days (Yeung et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial migration too could have been influenced by the fibrin glue applied (Yeung et al 2016). This represented a retraction of the tissue, exposing the sclera/ episclera.…”
Section: Discussionmentioning
confidence: 99%
“…This can be delayed by the use of fibrin glue to attach the conjunctiva on to AM. Fibrin glue is known to mechanically interfere with the migration of cells, which starts only when the glue has lysed 30. In most cases the redirecting sheet of amnion begins to fall off between week 1 and 3 by which time the cornea is substantially resurfaced by limbal explant-derived epithelium, making ingress of conjunctival epithelial cells much less likely due to contact inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Kheirkhah and colleagues suggested that the glue forms a full contact seal between the transplanted AM and the corneal surface, ensuring reepithelialization occurs on the surface of the AM rather than underneath, taking full advantage of the AM microenvironment . in vitro work has shown that fibrin glue inhibits cell migration, which in SLET may prevent ingrowth of conjunctival tissue at a critical phase and promote expansion of epithelial cells from explants on the AM surface . Growth rates vary between explants from the same donor placed in the same eye, which may be attributed to the amount of fibrin glue used for their individual attachment or to differences in handling during transplant .…”
Section: Mechanism Of Regenerationmentioning
confidence: 99%
“…57 in vitro work has shown that fibrin glue inhibits cell migration, which in SLET may prevent ingrowth of conjunctival tissue at a critical phase and promote expansion of epithelial cells from explants on the AM surface. 58 Growth rates vary between explants from the same donor placed in the same eye, which may be attributed to the amount of fibrin glue used for their individual attachment or to differences in handling during transplant. 4 Fibrin glue has also been shown to extend the beneficial effects of AM by delaying its breakdown compared with sutures.…”
Section: Mechanism Of Regenerationmentioning
confidence: 99%